Green consumption and sustainable lifestyle: Evidence from India - Rosario Florence Kennedy; Sahayaselvi Susainathan; Hesil Jerda George; Satyanarayana Parayitam (Administrative Sciences, 2024)
This study aims to comprehensively investigate the impact of green consumption on adopting a sustainable lifestyle. Based on the theory of planned behavior (TPB), a simple conceptual model is developed, and hypothesized relationships are tested in the context of a developing country- India. Using proportionate stratified random sampling, data were collected from 422 respondents from five districts in Tamil Nadu, southern India. First, the psychometric properties of the survey instrument were tested by PLS-SEM, and hypotheses were tested using path analysis. The findings show that (i) green product literacy (GPL) is not associated with green product purchase attitude (GPPA), (ii) green product orientation (GPO) is positively related to GPA, and (iii) social influence is positively associated with GPA. The results also indicate that GPA is a precursor to green purchase behavior (GPB), resulting in a sustainable lifestyle. This study found that social influence strengthens the positive effect of GPO on GPPA. From a practical standpoint, this study can provide valuable insights for policymakers, businesses, and organizations aiming to promote sustainable lifestyles by encouraging green consumption. As with any survey research, common method and social desirability biases can be significant limitations. However, every effort has been made to minimize these biases. To the best of our knowledge, the conceptual model is developed and tested for the first time, particularly in the context of a developing country-India. Thus, this study makes a unique contribution to the literature on sustainability.
Keywords: 350; green consumption; sustainable lifestyle; green purchase behavior; green purchase attitude